Evaluation of control methods for Acusta tourannensis (Souleyet,1842) (Gastropoda: Camaenidae) infesting dragon fruit (Selenicereus spp.) in Vietnam - Ngo, Dung Van; Pham, Hien Hong; Thoa, Ha Thi Kim; Nguyen, Hoa Thi; Joshi, Ravindra Chandra; Hoat, Trinh Xuan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Dragon fruit (Selenicereus spp.) cultivation in Vietnam faces severe losses due to Acusta tourannensis infestations, impacting yield and fruit quality. This study evaluated the efficacy of various control methods through field and greenhouse experiments in Binh Thuan Province, Vietnam, in 2023. Cultural practices, including reduced irrigation, herbicide application, and grass cutting, effectively suppressed snail populations by creating unfavorable conditions. Mechanical and manual removal methods, although useful, were labor-intensive. Bait trapping with dragon fruit parts was highly effective in capturing snails. Biological control using duck release significantly reduced snail densities, though contamination risks remain a concern. Botanical control with Saponin HF achieved mortality rates of 86.7–96.7% within 7–14 days. Chemical control with metaldehyde and niclosamide provided up to 100% mortality but necessitates careful management due to environmental risks. Integrated pest management (IPM) combining cultural, biological, and botanical control methods offers the most sustainable approach for managing A. tourannensis in dragon fruit orchards. Further research should focus on optimizing application rates and timing, developing eco-friendly alternatives such as plant-derived molluscicides, and assessing the long-term ecological impacts of these strategies. Enhancing these approaches will contribute to the effective and sustainable management of A. tourannensis, ensuring the viability of dragon fruit cultivation in Vietnam.